2009
DOI: 10.1136/gut.2008.169052
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease-associated risk variants in TNFAIP3 and REL implicate altered NF- B signalling

Abstract: Both TNFAIP3 (A20, at the protein level) and REL are key mediators in the nuclear factor kappa B (NF-kappaB) inflammatory signalling pathway. For the first time, a role for primary heritable variation in this important biological pathway predisposing to coeliac disease has been identified. Currently, the HLA risk factors and the 10 established non-HLA risk factors explain approximately 40% of the heritability of coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 28 publications
(37 reference statements)
4
125
2
1
Order By: Relevance
“…8 The region of interest spans B102 to 122 Mb and is clearly distinct from the HLA region as well as from the previously identified TNFAIP3 and TAGAP celiac susceptibility genes. 9,10 An independent study by Einarsdottir et al (unpublished) of susceptibility genes for celiac disease in Finnish and Hungarian families also showed linkage to 6q16-22, to a region overlapping with the linkage found in the Dutch population. Taken together, these results indicate the possibility of a genetic factor within the chromosome 6q21-22 region that is involved in susceptibility to celiac disease in multiple populations.…”
Section: Introductionmentioning
confidence: 99%
“…8 The region of interest spans B102 to 122 Mb and is clearly distinct from the HLA region as well as from the previously identified TNFAIP3 and TAGAP celiac susceptibility genes. 9,10 An independent study by Einarsdottir et al (unpublished) of susceptibility genes for celiac disease in Finnish and Hungarian families also showed linkage to 6q16-22, to a region overlapping with the linkage found in the Dutch population. Taken together, these results indicate the possibility of a genetic factor within the chromosome 6q21-22 region that is involved in susceptibility to celiac disease in multiple populations.…”
Section: Introductionmentioning
confidence: 99%
“…This study tested for association to approximately 310,000 single-nucleotide polymorphisms (SNPs) and identified a single risk locus in an LD block harboring IL2-IL21. Two follow up studies on the same sample (Hunt et al 2008;Trynka et al 2009) identified an additional nine non-HLA loci. A later CD GWAS by Dubois and colleagues (2010) included over 4,500 CD cases and over 11,000 controls from four populations (Finland, Italy, the Netherlands, the UK).…”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%
“…(SLE), rheumatoid arthritis, psoriasis, and celiac disease (24)(25)(26)(27)(28)(29). While only one missense coding allele has been identified thus far (in SLE), the wellestablished antiinflammatory functions of A20 in mice suggest that hypomorphic function or expression of A20 may contribute to the pathophysiology of these human conditions (24).…”
Section: A20 In Lymphocytesmentioning
confidence: 99%